BRCA1 Mutations and Their Consequences in Multiple Cancers: Molecular Insights and Emerging Therapeutic Strategies - Pandey, Swaroop Kumar; Paliwal, Swarnima; Mall, Braj Bhushan (Current Cancer Therapy Reviews, 2026)
Cancer is a global health burden, contributing significantly to the rising mortality rates across various forms of the disease. Identifying the underlying cause of this ailment is crucial to finding a way to save numerous lives worldwide. The <span class=
Keywords: BRCA1